2016
DOI: 10.1371/journal.pone.0168534
|View full text |Cite
|
Sign up to set email alerts
|

Enjoyment for High-Intensity Interval Exercise Increases during the First Six Weeks of Training: Implications for Promoting Exercise Adherence in Sedentary Adults

Abstract: This is the first study to show that enjoyment for high-intensity interval exercise increases with chronic training. Prior acute studies typically report high-intensity interval training (HIT) as being more enjoyable than moderate continuous training (MCT) unless the high-intensity intervals are too strenuous or difficult to complete. It follows that exercise competency may be a critical factor contributing to the enjoyment of HIT, and therefore building competency through chronic training may be one way to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
80
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(85 citation statements)
references
References 23 publications
3
80
0
2
Order By: Relevance
“…), but importantly enjoyment of HIT increases as participants progress through a training programme (Heisz et al . ). Therefore, unlike previous low‐volume HIT studies (Little et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…), but importantly enjoyment of HIT increases as participants progress through a training programme (Heisz et al . ). Therefore, unlike previous low‐volume HIT studies (Little et al .…”
Section: Discussionmentioning
confidence: 97%
“…This allowed participants to modify exercise sessions, choosing exercises that elicited the desired HR response, but were suitable for their level of mobility and fitness. In addition, recent studies have suggested that sedentary individuals report pleasant feelings during the first three of four bouts of low-volume HIT (Frazão et al 2016), but importantly enjoyment of HIT increases as participants progress through a training programme (Heisz et al 2016). Therefore, unlike previous low-volume HIT studies Tan et al 2018), the current intervention started with a low number of intervals and progressed training volume throughout (4 intervals during week 1-2 to 8 intervals during week 11-12).…”
Section: Myocyte Adaptationsmentioning
confidence: 99%
“…This may potentially be explained by our present finding that the affective responses to REHIT significantly improve during a training intervention. Indeed, enjoyment has been shown to increase progressively during 6 weeks of HIIT but remain constant during 6 weeks of MICT (Heisz, Tejada, Paolucci, & Muir, 2016). Alternatively, it is possible that shorter exposure duration (40 s for REHIT vs 30 min for MICT) may result in a preference for REHIT despite it being perceived as less enjoyable.…”
Section: Discussionmentioning
confidence: 99%
“…The finding that increasing exercise intensity has a negative effect on adherence is in accordance with an earlier review by Dishman et al, who concluded that high‐intensity activities may negatively influence behavior. However, these findings are contrary to the popular idea that HIIT may be a more viable, time‐efficient option to increase adherence to exercise . In interpreting these findings, it should be considered that while our primary meta‐analysis attempted to isolate the independent effect of intensity and time manipulation, HIIT training typically simultaneously increases intensity while decreasing time.…”
Section: Discussionmentioning
confidence: 67%